THE RESULTS OF A RETROSPECTIVE ANALYSIS OF THE INFORMATIVE VALUE OF VARIOUS DIAGNOSTIC METHODS FOR ADENOMYOSIS - Mukhammadjonova M. M.; Gafurova F. A. (Web of Journals Publishing, 2025)
In recent years, there has been a significant increase in the frequency of adenomyosis, and it is more often diagnosed in the late stages (stage III–IV), which pose a serious threat to the health of patients, including reproductive ones. Currently, there are no research methods that make it possible to verify early-stage adenomyosis non-invasively and with a high degree of informativeness. It is advisable to conduct comprehensive clinical, morphological and immunohistochemical studies to improve the early noninvasive diagnosis of this disease.